PERMANENT EDUCATION IN HEALTH: PERCEPTION OF PROFESSIONALS IN THE MULTIDISCIPLINAR RESIDENCE - Cristiane Trivisiol da Silva; Valquíria Toledo Souto; Camila Castro Roso; Marlene Gomes Terra (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211067 Aim: to know the perception of professional members of a multiprofessional residence about permanent education in health. Method: the study is characterized as a qualitative, descriptive and exploratory research, type case study, conducted through field observation, documentary research and semi-structured interview, with 17 professionals members of a multiprofessional residence. Results: the evidence shows that the multiprofessional residence in health it's a space that enables integration theory and practice as a trigger of Continuing Education in Health, which, in turn, is articulated by segments of attention for the production and management of health. Conclusion: it's highlightened the perception of permant education beyond a punctual perspective, being trigged by spaces in which the actors discuss about permanent education, so that it can contribute to the development of competencies to act on the Public Health System.